Non-invasive Assay for Measurement of Fecal Triiodothyronine (T3) Metabolite Levels in European Mouflon (Ovis aries musimon) - Pasciu, Valeria; Nieddu, Maria; Baralla, Elena; Muzzeddu, Marco; Porcu, Cristian; Sotgiu, Francesca Daniela; Berlinguer, Fiammetta (Frontiers in Veterinary Science, 2022)
Thyroid hormones (THs) are important indicators of metabolism and animal health. Traditionally, they have been determined from blood or urine samples. However, as their collection may be stressful and requires ethical approval, alternative non-invasive matrices are preferred when dealing with wild animals. Triiodothyronine (T3) is the active form of THs in blood and the major metabolite excreted in faeces. This creates the ideal conditions for its assay in faecal samples. Faecal sampling eliminates the stress of the animals and the need to physically capture them. However, in wild species it is rare to find species-specific kits for the hormone assay. So, the objective of this work was to validate a method for the quantification of T3 metabolite (FTM) levels in faeces of European mouflon by using an economic and easily available ELISA kit designed to quantify T3 in human plasma. Analytical and biological validations were performed in faeces collected from 10 mouflons (5 ewes and 5 rams). An efficient liquid-extraction method was optimized. Precision, dilution linearity, parallelism, recovery and stability of T3 in faecal samples were calculated. Obtained data were considered acceptable according to international guidelines. The reliability of the results was verified comparing human plasma and mouflon faecal samples fortified with the same T3 standard solutions. The biological validation showed higher FTM levels in March compared to June, and no differences between mouflon ewes and rams. The validation of the present method provides a non-invasive and affordable tool for the quantification of FTM in European mouflon.